DOP39 Effect of baseline disease characteristics on clinical outcomes in moderate-to-severe Ulcerative Colitis treated with upadacitinib: Results from a Phase 3 trials programme. (21st January 2022) - Higgins, P; Colombel, J F; Reguiero, M; Parkes, G; Ilo, D; Philips, C; Yao, X; Cheng, E; Schreiber, S
Abstract: Background: Upadacitinib (UPA) is an oral, once-daily (QD), selective Janus kinase inhibitor that has demonstrated efficacy in the induction and maintenance treatment of Ulcerative Colitis (UC). This analysis aimed to assess the impact of baseline UC characteristics on clinical outcomes following UPA therapy. Methods: Patients (pts) with moderately to severely active UC who had failed conventional or biological treatment were enrolled in two randomised, double-blind (DB), placebo (PBO)-controlled, Phase 3, 8-week induction studies of UPA 45 mg QD vs PBO. Pts achieving a clinical response (decrease from baseline in Adapted Mayo score ≥2 points and ≥30% from baseline, plus a decrease in rectal bleeding score [RBS] ≥1 or an absolute RBS ≤1) at Week (Wk) 8 entered a 52-week, randomised, DB, PBO-controlled, Phase 3 maintenance study, and received UPA 15 mg QD, UPA 30 mg QD, or PBO. The primary efficacy endpoint was clinical remission per Adapted Mayo score at Wk 8 (induction) and at Wk 52 (maintenance). Pre-specified (PS) and post hoc (PH) analyses were conducted by baseline disease activity (full Mayo score ≤9 or >9) (PS), extent (PS), duration (<2, 2–5, >5–10, >10 years [yrs]) (PH), and high-sensitivity C-reactive protein (hs-CRP) level (≤5 or >5 mg/L) (PH). Results: 988 pts were included in the induction studies, and 451 in the maintenance study. The treatment difference between UPA 45 mg QD and PBO excluded zero for all subgroups at Wk 8 (Figure 1). Wk 8 remission rates were lower for full Mayo score >9 vs ≤9, and for CRP >5 vs ≤5 mg/dL, with minimal effects of disease extent or duration. Wk 52 maintenance of remission rates were greater with UPA 15 mg and 30 mg QD vs PBO (16–44% and 30–50% difference, respectively), and with UPA 30 vs UPA 15 mg QD. This incremental benefit of the 30 mg dose was greater in pts with severely (full Mayo score >9) vs moderately active disease (Figure 2); 15 mg and 30 mg demonstrated similar efficacy in pts with Mayo score <9. Statistically non-significant numerical advantages for UPA 30 mg vs UPA 15 mg maintenance were seen in all subgroups, with the exception of hs-CRP >5 mg/L. Conclusion: UPA 45 mg QD is an effective induction treatment for UC, regardless of baseline disease characteristics. Both 15 and 30 mg UPA doses are effective maintenance regimens, regardless of baseline disease characteristics. However, the 30 mg dose shows a trend towards increased benefit vs 15 mg in pts with Mayo score >9 and extensive disease. This analysis suggests that while UPA 15 mg may be most appropriate for patients with UC with a low inflammatory burden (per full Mayo score and extent), the 30 mg dose may be more appropriate for those with a high one.